Guatemalan Spanish in contact: Prosody and intonation - Yolanda Congosto Martín (Estudios de Fonética Experimental)
This study forms part of the Geoprosadic project: the Geoprosodic and Sociodialectal Study of North American Spanish. The main objective of this project is to describe and compare the prosody of three geographical areas, Los Angeles, Mexico and Guatemala, that are closely related historically, socially and linguistically due to the contact established over time and the coexistence of people and cultures. The sole aim is to examine the prosodic differences between the Spanish spoken by Latin American people living in Los Angeles (mainly Mexicans, Salvadorans and Guatemalans) and the Spanish spoken by those who have never left their native countries, and to compare whether the spatio-temporal distance of the former and their immersion in a different sociolinguistic sphere, in contact with the English language and other varieties of Spanish, have brought about differences of a geoprosodic nature. In this case, the study focuses on the Guatemalan Spanish of various speakers. From a methodological point of view, the research is linked to the international project AMPER. The analytical methods of AMPER are followed and the research is limited to the study of female intonation and sentences with a subject–verb–object (SVO) structure from corpus 1 (declaratives and absolute interrogatives). The results of this research corroborate the initial hypothesis and establish the melodic differences between both groups of speakers, particularly regarding declaratives.